2003
DOI: 10.1523/jneurosci.23-12-04967.2003
|View full text |Cite
|
Sign up to set email alerts
|

Oligodendrocytes Promote Neuronal Survival and Axonal Length by Distinct Intracellular Mechanisms: A Novel Role for Oligodendrocyte-Derived Glial Cell Line-Derived Neurotrophic Factor

Abstract: Interactions of CNS cells lead to the establishment of complex neural systems. Specifically, oligodendrocytes form myelin sheaths around axons that enable rapid electrical conduction of impulses. Recent evidence has emerged that oligodendrocytes may also release trophic factors promoting neuronal survival. We therefore studied the effects of factors released from cells of the oligodendrocyte lineage on neuronal survival and also on the morphology of neurons. Neurons derived from rat embryonic cortices were cul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
219
1
2

Year Published

2004
2004
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 279 publications
(225 citation statements)
references
References 47 publications
3
219
1
2
Order By: Relevance
“…94,95 Fifth, a reduction in the number and function of oligodendrocytes is becoming apparent from ultrastructural, 96 morphometric 97,98 and microarray 99,100 studies. Given the role of oligodendrocytes in myelination and other aspects of neuronal and synaptic integrity, 97,101,102 their involvement in schizophrenia is likely to be inextricably linked to the neuronal alterations mentioned, and to the functional consequences thereof, but at present it is not clear which are primary changes and which are secondary. Moreover, oligodendrocytes are an especially vulnerable cell population to many insults, and molecular abnormalities of oligodendrocytes are reported in association with many CNS disorders not involving myelin directly.…”
Section: Histological Findingsmentioning
confidence: 99%
“…94,95 Fifth, a reduction in the number and function of oligodendrocytes is becoming apparent from ultrastructural, 96 morphometric 97,98 and microarray 99,100 studies. Given the role of oligodendrocytes in myelination and other aspects of neuronal and synaptic integrity, 97,101,102 their involvement in schizophrenia is likely to be inextricably linked to the neuronal alterations mentioned, and to the functional consequences thereof, but at present it is not clear which are primary changes and which are secondary. Moreover, oligodendrocytes are an especially vulnerable cell population to many insults, and molecular abnormalities of oligodendrocytes are reported in association with many CNS disorders not involving myelin directly.…”
Section: Histological Findingsmentioning
confidence: 99%
“…Similar improvements have been demonstrated by administration of neuroprotective agents (for example, MgCl 2 and vitamin B 3 ), suggesting that neuroprotective mechanisms may be involved (30,(57)(58)(59). Several studies have shown that media from neural cell cultures provides beneficial effects by transfer of neurotrophic factors (17,60). Indeed, in a recent follow-up study (unpublished observations), we showed that transplanted ES cells are a source of BDNF and IL-6 and increased cAMP in the injured host cells in the spinal cord.…”
Section: Discussionmentioning
confidence: 52%
“…Because PrP C binds in vitro to the transmembrane and GPI-linked forms of NCAM (Schmitt-Ulms et al, 2001), it might contribute to the very same pathways. Alternatively, PrP C may instruct oligodendrocytes to release factors necessary for axonal survival (Wilkins et al, 2003). Direct toxicity of ⌬PrP and Dpl to oligodendrocytes seems to be unlikely, because we did not observe oligodendrocytic cell death or ultrastructural abnormalities in oligodendrocytes.…”
Section: Discussionmentioning
confidence: 74%